2023
DOI: 10.3390/foods12152962
|View full text |Cite
|
Sign up to set email alerts
|

Novel Approaches to Improve Meat Products’ Healthy Characteristics: A Review on Lipids, Salts, and Nitrites

Sandra S. Q. Rodrigues,
Lia Vasconcelos,
Ana Leite
et al.

Abstract: Meat products are a staple of many diets around the world, but they have been subject to criticism due to their potential negative impact on human health. In recent years, there has been a growing interest in developing novel approaches to improve the healthy characteristics of meat products, with a particular focus on reducing the levels of harmful salts, lipids, and nitrites. This review aims to provide an overview of the latest research on the various methods being developed to address these issues, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 121 publications
1
2
0
Order By: Relevance
“…Corral et al [5] also showed the latter results. Independent of these indifferent results, some review publications support our results indicating a negative correlation between NaCl content and a w values [1,12,20]. Water activity is defined as the ratio between the vapor pressure of a given food in relation to the vapor pressure of pure water at the same temperature [12].…”
Section: Ripening Loss a W Valuessupporting
confidence: 69%
“…Corral et al [5] also showed the latter results. Independent of these indifferent results, some review publications support our results indicating a negative correlation between NaCl content and a w values [1,12,20]. Water activity is defined as the ratio between the vapor pressure of a given food in relation to the vapor pressure of pure water at the same temperature [12].…”
Section: Ripening Loss a W Valuessupporting
confidence: 69%
“…Hemp flour is produced from hemp seeds that have a high phenolic content and exhibit good antioxidant activity [34,61]. Additionally, hemp seeds mainly contain γ-tocopherol and lower amounts of α-tocopherol, both known for their antioxidant activity [27,62]. The effects of various plant-based additives, including extracts and powders, either alone or in combination with sodium nitrite with respect to limiting lipid oxidation in meat products has been well documented in recent reviews by Ferysiuk and Wójciak [10] and Stoica et al [25].…”
Section: Lipid Oxidationmentioning
confidence: 99%
“…However, currently goat meat is mainly used in home cooking, industrial processing due to the lack of technological development does not allow the full is necessary to ensure the shelf life of finished sausages. This is possible due to the addition of natural sources of natural antioxidants [33]. Children are a more vulnerable group of consumers, and products for them must meet high food safety standards [34].…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%